Denitrification performance of Pseudomonas fluorescens Z03 immobilized by graphene oxide-modified polyvinyl-alcohol and sodium alginate gel beads at low temperature. Issue 3 (4th March 2020) - Tang, Meizhen; Jiang, Jie; Lv, Qilin; Yang, Bin; Zheng, Mingna; Gao, Xin; Han, Jindi; Zhang, Yingjie; Yang, Yuewei
Abstract : Improving the effect of microbial denitrification under low-temperature conditions has been a popular focus of research in recent years. In this study, graphene oxide (GO)-modified polyvinyl-alcohol (PVA) and sodium alginate (SA) (GO/PVA–SA) gel beads were used as a heterotrophic nitrification–aerobic denitrification (HN–AD) bacteria ( Pseudomonas fluorescens Z03) carrier to enhance nitrogen removal efficiency levels at low temperatures (6–8°C). The removal efficiency of N H 4 + -N and N O 3 − -N and the variations in concentrations of extracellular polymeric substances (EPS) under different GO doses (0.03–0.15 g l −1 ) were studied. The results indicated that the addition of GO can improve the efficiency of nitrogen removal, and the highest removal efficiency level and highest carbohydrate, protein, and total EPS content levels (50.28 mg, 132.78 mg and 183.06 mg (g GO/PVA–SA gel) −1, respectively) were obtained with 0.15 g l −1 GO. The simplified Monod model accurately predicted the nitrogen removal efficiency level. These findings suggested that the application of GO serves as an effective means to enhance nitrogen removal by stimulating the activity of HN–AD bacteria.